Pengaruh Bauran Pemasaran Terhadap Keputusan Mahasiswa Dalam Memilih Program Study Administrasi Bisnis Politeknik Sawunggalih Aji -Purworejo - Danis Imam Bachtiar; Aulia Fahrianti (Politeknik Sawunggalih Aji, 2022)
Effect of Marketing Mix on Student Decision in Choosing Sawunggalih Aji Purworejo Polytechnic Business Administration Study Program, Aulia Fahrianti, July 2017, 114 pages + xix +attachments. In the world of education, especially in colleges, there should be a study of marketing mix to attract new prospective students. In Sawunggalih Aji Purworejo Polytechnic, the number of new students of Business Administration Studies Program tend to be unstable and even experiences a very significant decrease. To find out how much marketing mix factor especially product, price, place, promotion, and physical evidence influence student’s decision to choose Business Administration Study Program, a research is needed. The research used is a questionnaire with validity test analysis, reliability and multiple linear regression. The result of the validity and reliability test are all item declared valid because the result of each test value rcount > 0.320 and reliable because the value af Alpha > 0.6. Result of regression: Y = 140,987 + 0,12 X1 + 0,081 X2 + 0,178 X3 + (- 0,025) X4 + 0,15 X5. In addition, independent variables only affect 8% of the dependent variable. In the F (Anova) test the result Fcount 0,559 < value Ftable 2,518 meaning independent variables do not affect dependent variables. While in t test, each independent variables all have the value tcount < tables meaning that product variable, price, place, promotion and physical evidence have also no significant effects to students decision